Idiom: Politics of Jouissance as the Subjectivation of the Letter - René Lew (The European Journal of Psychoanalysis, 2024)
It will be the articulation that it induces and supports in order to pass from the signifiance (and from the phallic jouissance) to the object a (and to the plus-of-jouissance) ? and vice versa. I will develop ? in discussion with Néstor Braunstein ? the politics of the letter in connection with the passage from the S1 signifiance to the signifiers properly so called S2, from phallic jouissance to the jouissance of the Other and from the surplus-of-jouissance to the surplus-value. Yet there is no valorization of jouissance in the strict sense, nor is there any well-founded access to signifiers, nor is there any summation of plus-of-jouissance. From then on, the politics of the letter advocated by psychoanalysis is both of a different order and carries effects other than what is commonly called politics, which is a policy of exploitation and profit made at the expense of others. Psychoanalysis is impredicative, while politics is predicative. But, while the predicative rejects the imprecative (excluded third), the imprecative gives way to the predicative (included third, one might say, i.e. the Freudian structure of speech in “third person”, according to Freud).
Keywords: Lacan; braunstein; impredicative; signfier; signifiance